THE ROLE OF ENGLISH LANGUAGE AND COMMUNICATION IN ENGINEERING EDUCATION - Dr. S. Rajeswari, Ms. G.R Swathi, Mr. Baliya Sridhar (International Journal of Advanced Science and Technology, 2020)
English language education in Engineering focuses on training in specific domains of English to enrich technical knowledge base of students. English language and communication plays a vital role to be successful to seek dream job and communicate across borders. The present study analyses the role of English language and communication in engineering education. The findings are significant that communication skills impact on employability. The vital factors are parental care, skilled teachers, use of technology in teaching-learning process and technical competency with international vision. Proper utilization of online and offline resources transmits their cultural knowledge to research connecting global technical minds. The results suggest it is necessary for language teachers to bridge the gap between campus and company opening the uncharted line of investigation in the fields of technology. Academic curriculum must be designed aiming to motivate and yield research approach.